2021
DOI: 10.1507/endocrj.ej20-0377
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal thyroid hormone in late pregnancy on adverse birth outcomes: A retrospective cohort study in China

Abstract: The purpose of this study was to explore the impact of maternal thyroid hormone dysfunction in late pregnancy on birth outcomes in a Chinese population. We retrospectively examined hospitalisation records and laboratory data between April 2016 and March 2017 and obtained results from 11,564 consecutive pregnant women with singleton births in which serum thyroid hormone had been examined together with birth outcomes. We assessed the association between maternal thyroid level and dysfunction with adverse birth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The studies during 2013-2018 showed that the overall prevalence of GDM was 10-20% according to the IADPSG criteria [24][25][26]. Several types of research represented that the overall prevalence of PIH was less than 1% [27,28]. In general, the prevalence of hypertension was higher in cold areas than others [29].…”
Section: Discussionmentioning
confidence: 99%
“…The studies during 2013-2018 showed that the overall prevalence of GDM was 10-20% according to the IADPSG criteria [24][25][26]. Several types of research represented that the overall prevalence of PIH was less than 1% [27,28]. In general, the prevalence of hypertension was higher in cold areas than others [29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as suggested by a recent cohort study on the association between maternal thyroid hormone in late pregnancy and adverse birth outcomes, the rate of PTB in 11,564 Chinese pregnant women including those with major pregnancy complications was 6.9%, close to 7.0%. 20 Furthermore, PTB rate differs by regions in China, among which East China shows a lower PTB rate. 1 A low PTB rate in the East may be related to a higher socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective cohort study from China found that isolated hypothyroxinemia (decreased FT4 with normal TSH) was associated with an increased risk for SGA in the first 20 weeks of pregnancy ( 25 ). Yuan et al ( 26 ) reported that hyperthyroxinemia (increased FT4 with normal TSH) was associated with a decreased risk of LGA in late pregnancy. However, in the Ma'anshan birth cohort, maternal isolated hypothyroxinemia was not associated with an increased risk for SGA in either the first or the second trimester, and an increased risk of LGA was observed in the second trimester ( 27 ).…”
Section: Discussionmentioning
confidence: 99%